2004
DOI: 10.1111/j.1442-200x.2004.01826.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal resistive indexes and some renal functions in liver cirrhotic children

Abstract: We conclude that patients with cirrhosis are at risk of renal deterioration, which can not be detected by serum urea, creatinine, and glomerular filtration rate. The increase of RRI is associated with the progress of hepatocellular disease, and also the development of ascites and portal hypertension. Elevated urinary sodium excretion, elevated urinary NAG/Cr ratio and microalbuminuria might have a prognostic value especially in patients with Child scores> 6. Hence, monitoring RRI is a non-invasive means of stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Urinary NAG was significantly elevated in the MHRS model in the present study reflecting tubular dysfunction and kidney parenchymal damage as reported by Skálová (2005). In agreement with this result, high urinary NAG was reported in infants with liver cirrhosis (Aydogdu et al, 2004) pointing to an occurrence of renal dysfunction and HRS. The plasma albumin level was reduced significantly in MHRS rats in the present study which confirms the work of García-Martínez et al (2013), who showed that not only albumin concentration but also albumin function is reduced in liver failure.…”
Section: Discussionsupporting
confidence: 92%
“…Urinary NAG was significantly elevated in the MHRS model in the present study reflecting tubular dysfunction and kidney parenchymal damage as reported by Skálová (2005). In agreement with this result, high urinary NAG was reported in infants with liver cirrhosis (Aydogdu et al, 2004) pointing to an occurrence of renal dysfunction and HRS. The plasma albumin level was reduced significantly in MHRS rats in the present study which confirms the work of García-Martínez et al (2013), who showed that not only albumin concentration but also albumin function is reduced in liver failure.…”
Section: Discussionsupporting
confidence: 92%
“…High urinary NAG was found in patients with glycogen storage disease (39) and in children with iron overload in beta-thalassaemia major (45), in patients with Wilson's disease (70), in children with liver cirrhosis (7), with Lowe's syndrome (38) and in children with familial Mediterranean fever (4).…”
Section: Various Diseasesmentioning
confidence: 99%
“…LC is accompanied by hemodynamic changes which eventually lead to vasoconstriction of the renal vessels with marked decrease in renal perfusion and glomerular filtration rate (GFR), azotemia, and increased serum creatinine concentration 2,8,9 . This impairment of renal function in liver cirrhosis is known as hepatorenal syndrome (HRS), the development of which has poor prognosis and is associated with mortality rates approaching 100% 10 . Moreover, the only effective treatment is liver transplantation; 11 hence, early detection and management is essential for patient survival.…”
Section: Introductionmentioning
confidence: 99%